The effect of small games on improving some motor skills among primary school girls aged (9-10) years - Ibrahim, Prof. Dr. Ban Abdul Rahman (Sulaimani Journal for Humanities, 2026)
This research aimed to develop a recreational mini-games program for elementary school girls aged 9-10 years, and to identify the program's impact on developing certain motor skills in these girls. The research population, selected purposively, consisted of 30 third-grade elementary school girls aged 9-10 years. A random sample of 15 girls was selected from this population. The research methodology employed a single-group pre-test/post-test experimental design. The independent variable, the recreational sports program, was implemented with the research sample within the schoolyard. The Bordeaux Survey of Motor Abilities was the research instrument. This test was designed to detect cognitive developmental errors and identify perceptual-motor problems among the girls. The results showed that the program had a positive impact on developing the targeted motor skills in the schoolyard sample. Similarly, the tests administered during the program also had a positive effect on developing the motor skills of the same sample.